Distribution characteristics of selenium and heavy metal elements in soil-crop system in ankang, shaanxi, china - Li, Aorui; Chen, Jiping; Wang, Chi; Zhang, Zhimin; Wang, Hui; Ji, Huawei; Sun, Tianyu; Zeng , Zhaohua; He, Yaning (Bangladesh Journal of Botany, 2023)
A total of 229 groups of root vegetables, rice, corn and their root soils were collected in Ankang, Shaanxi, to analyze the characteristics of element migration and transformation in crops and root soil, to compare the migration and enrichment capabilities of various elements in different crops, to explain the characteristics of root soil pH and element correlation, and provide a theoretical basis for agricultural development. Results showed that there were differences in the ability of crops to accumulate various elements in the soil. The absorption capacity of Se, Cd and Zn elements was strong, while the bioaccumulation ability of As, Pb and Cr elements was weak. The contents of Cr, As and Hg were the highest in rice, which were significantly higher than those in root vegetables and corn. The contents of Cd, Cu and Pb in root vegetables were the highest, significantly higher than those in rice and corn. The content of various elements in crops and root soil had a different intensity correlation. Generally speaking, the content of various elements in crops increased with the increase of root soil element content to a certain extent. There was a negative correlation between pH and soil elements, and there was a significant positive correlation between the elements in the root soil of different crops. Bangladesh J. Bot. 52(2): 649-657, 2023 (June) Special